أوربا وثنائية الإغراء والإقصاء في رواية البعيدون لبهاء الطود - دريدي, فريدة (University of Eloued جامعة الوادي, 2018)
تهدف هذه الدراسة إلى معالجة إشكالية صراع الحضارات في رواية البعيدون للروائي المغربي بهاء الطود، الذي أعطى لتيمة الصراع الحضاري القائم على ثنائيات ضدية أبعادا إيديولوجية تشرح واقع العلاقة المضطربة بين الأوربي والعربي وبالتحديد الإفريقي، انطلاقا من معالجة موضوع الهجرة، الذي يعكس طبيعة الصراع، كما تهدف الدراسة إلى توضيح إمكانية أن تحول الصراع الحضاري في الرواية إلى حوار ثقافي مبني على الأخذ والعطاء ويدعو إلى التسامح و المصالحة بين الأنا والآخر . Abstract: This literary study to deal with the problem of the clash of civilizations in the novel "El Baidoun" Moroccan novelist " Baha Ettod", linking the theme of conflict to the dialectic of the ego and the Other, as antithetical binary explaining the reality of the relationship trouble between the European and the Arab and especially that of Africa, starting with the treatment of the immigration issue which reflects the nature of the conflict. This study also aims to clarify the possibility of the transformation of cultural conflict in the novel into a cultural dialogue based on exchange and interaction, and calls for tolerance and reconciliation between self and other.
Europe and dualism temptation and exclusion in the novel " El Baidoun " of Baha Ettod
مجلة البحوث والدراسات المجلد 15 العدد02 جامعة الوادي
Keywords: صراع الحضارات؛ الأنا؛ الآخر الأوربي؛ الإفريقي؛الهجرة؛الإغراء؛الإقصاء; clash of civilizations, the me , the other , the european , African, immigration , temptation , exclusion